Lithium‐Ion Batteries: From an Enhanced Understanding to Commercially Viable Electrodes: The Case of PTCLi4 as Sustainable Organic Lithium‐Ion Anode Material (Adv. Sustainable Syst. 3‐4/2017). (April 2017) - Iordache, Adriana; Bresser, Dominic; Solan, Sébastien; Retegan, Marius; Bardet, Michel; Skrzypski, Jonathan; Picard, Lionel; Dubois, Lionel; Gutel, Thibaut
Abstract : Organic active materials provide great opportunities for lower cost and enhanced sustainability of next generation rechargeable batteries. In article number 1600032, Lionel Picard, Thibaut Gutel, and co‐workers provide new insights into the underlying reaction mechanisms, and demonstrate the feasibility of realizing commercially viable electrodes for organic lithium batteries.